The influence of psychological factors on post‐partum weight retention at 9 months. (26th October 2013) - Phillips, Joanne; King, Ross; Skouteris, Helen
<x xml:space="preserve">Abstract</x> Objectives Post‐partum weight retention (PWR) has been identified as a critical pathway for long‐term overweight and obesity. In recent years, psychological factors have been demonstrated to play a key role in contributing to and maintaining PWR. Design Therefore, the aim of this study was to explore the relationship between post‐partum psychological distress and PWR at 9 months, after controlling for maternal weight factors, sleep quality, sociocontextual influences, and maternal behaviours. Method Pregnant women (N = 126) completed a series of questionnaires at multiple time points from early pregnancy until 9 months post‐partum. Results Hierarchical regression indicated that gestational weight gain, shorter duration (6 months or less) of breastfeeding, and post‐partum body dissatisfaction at 3 and 6 months are associated with higher PWR at 9 months; stress, depression, and anxiety had minimal influence. Conclusion Interventions aimed at preventing excessive PWR should specifically target the prevention of body dissatisfaction and excessive weight gain during pregnancy. Statement of contribution What is already known on this subject? Post‐partum weight retention (PWR) is a critical pathway for long‐term overweight and obesity. Causes of PWR are complex and multifactorial. There is increasing evidence that psychological factors play a key role in predicting high PWR. What does this study add? Post‐partum body dissatisfaction at 3 and 6 months is associated with PWR at 9 months post‐birth. Post‐partum depression, stress and anxiety have less influence on PWR at 9 months. Interventions aimed at preventing excessive PWR should target body dissatisfaction.